Perancangan Aplikasi “Empatiku” Berbasis Android Untuk Peningkatan Aksesibilitas Informasi Bagi Penyandang Disabilitas - Rahman, Rakhmadi; I, Ikbal; V, Viandra; Azzahra, Maryam (Madani: Jurnal Ilmiah Multidisiplin, 2024)
In an increasingly advanced digital era, technology has a very important role in increasing information accessibility for all individuals, including people with disabilities. One approach that has proven effective in improving their quality of life is the development of Android-based applications specifically designed to meet their needs. This article discusses the design of the "EmpatiKu" application which aims to increase information accessibility for people with disabilities, with a focus on the use of technology to support independence and social inclusion. The development of information and communication technology has opened up new opportunities in efforts to overcome the challenges of information accessibility for people with disabilities. The "EmpatiKu" application is designed to present innovative solutions that utilize the power of Android as the main platform. Using features such as voice recognition, disability-friendly navigation, and an easy-to-access interface, the app aims to provide a bridge to information often encountered by those with physical or sensory limitations.